2021
DOI: 10.32534/jsfk.v15i02.2293
|View full text |Cite
|
Sign up to set email alerts
|

TRUTH & POST TRUTH DEWASA INI

Abstract: Artikel ini berusaha menganalisis konsep mengenai kebenaran dan pasca kebenaran dalam kajian filsafat dikaitkan dengan kajian kontekstual. Perkembangan pemikiran dan ilmu pengetahuan manusia seolah tidak pernah berakhir, pasalnya perkembangan apa yang dianggap benar dewasa ini berbeda dengan apa yang dianggap benar pada masa sebelumnya. Perkembangan zaman dewasa ini yang sering disebut sebagai postmodernisme yang di dalamnya termasuk dalam banyaknya penemuan-penemuan yang dilakukan oleh manusia terutama mengen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This methodology was carried out using a descriptive analysis approach, documentation analysis, and so on (Bhaskaran et al, 2017;Chair & Adzfar , 2021;MacKenzie & Bhatt, 2020;Romano, 2017;Rosůlek, 2019;Yerlikaya & Aslan, 2020). This was followed by 7 literature review articles (Ar Razy & Zakaria, 2021;Muqsith & Pratomo, 2021;Rügenhagen et al, 2020;Suharyanto, 2019;Yujie et al, 2022). And there are only 2 articles that use mixed methodology (Cheng et al, 2021;Moravec et al, 2019).…”
Section: Methodology Patternsmentioning
confidence: 99%
See 4 more Smart Citations
“…This methodology was carried out using a descriptive analysis approach, documentation analysis, and so on (Bhaskaran et al, 2017;Chair & Adzfar , 2021;MacKenzie & Bhatt, 2020;Romano, 2017;Rosůlek, 2019;Yerlikaya & Aslan, 2020). This was followed by 7 literature review articles (Ar Razy & Zakaria, 2021;Muqsith & Pratomo, 2021;Rügenhagen et al, 2020;Suharyanto, 2019;Yujie et al, 2022). And there are only 2 articles that use mixed methodology (Cheng et al, 2021;Moravec et al, 2019).…”
Section: Methodology Patternsmentioning
confidence: 99%
“…44 From the table representation above, it can be concluded that most of the authors of articles on this theme use journal article types. A total of 44 authors discussed journals related to themes regarding the new media phenomenon (Singh et al, 2022), the impact resulting from the spread of fake news on social media (Douai, 2019;Harjuniemi, 2022;Yerlikaya & Aslan, 2020), the development of the phenomenon post truth (Ar Razy & Zakaria, 2021;Mudawamah, 2018;Rianto, 2020), what are the implications of the post truth concept in the current digital era (Harjuniemi, 2022;Krasni, 2020;Mróz, 2017;Mudawamah, 2018;Rianto, 2020;Romano, 2017;Salman et al, 2019), to what attitude needs to be taken in dealing with the spread of post truth (Moravec et al, 2019;Rodríguez-Pérez et al, 2021).…”
Section: Author Distribution Patternsmentioning
confidence: 99%
See 3 more Smart Citations